E-learning in Business Practice, a Case Study During COVID-19 in Croatia (Informatica, 2020)
Technological progress is increasingly changing the form of learning and communication in the business environment. The omnipresence of computers enables distance learning to an increasing number of people, whose systematic use is enabled primarily via various e-learning platforms. To be a market competitive, companies must be ready for fast changes and constant adaption to the new technologies. This paper provides a brief classification of e-learning its features and its content as well as an overview of the presence of e-learning in the companies from the Republic of Croatia via a survey that we conducted among 80 of them. The results of the survey are particularly important since they were collected during the COVID-19 pandemic when companies were abruptly forced to adapt to working from home. The primary goal of the survey was to analyze to which extent they use e-learning for their daily business and education of the employees. The survey also shows what services do they use and prefer the most and what is their overall opinion about e-learning in business.Technological progress is increasingly changing the form of learning and communication in the business environment. The omnipresence of computers enables distance learning to an increasing number of people, whose systematic use is enabled primarily via various e-learning platforms. To be a market competitive, companies must be ready for fast changes and constant adaption to the new technologies. This paper provides a brief classification of e-learning its features and its content as well as an overview of the presence of e-learning in the companies from the Republic of Croatia via a survey that we conducted among 80 of them. The results of the survey are particularly important since they were collected during the COVID-19 pandemic when companies were abruptly forced to adapt to working from home. The primary goal of the survey was to analyze to which extent they use e-learning for their daily business and education of the employees. The survey also shows what services do they use and prefer the most and what is their overall opinion about e-learning in business